Sikap Politik Elit Muhammadiyah dan Nahdlatul Ulama di Surakarta tentang Pemilihan Presiden secara Langsung (Sebuah Studi Komparatif) - Sumaji, Muhammad Anis (2016)
ABSTRACT Anxiety and attitude of the elite Muhammadiyah and Nahdlatul Ulama in Surakarta in particular on the process of direct presidential elections be interesting to study related to the pattern of movement organization that brings together the missionary movement enjoining and forbidding the evil and innocent of practical politics, but there is freedom for Muhammadiyah and Nahdlatul Ulama elite to act individually at the level of practical politics, giving rise to diverse attitudes. The attitude of the political elite Muhammadiyah and Nahdlatul Ulama in Surakarta on direct presidential elections are grouped in three variants attitude namely: first, moderation idealistic which have characteristics, among others, the orientation of his attitude towards the Islamic ideals is an ideal Islamic accordance with Al-Quran and Sunnah, Second, realistic-critical attitude is characterized among other things see the connection between the substantive dimensions rather than religious doctrine, the social context of the community. Third, a pragmatic attitude-accommodating attitude that has characteristics, among others, put in the position of co-operative attitude, sometimes even compromise with the parties that a group is advantageous. The attitude of the political elite, this is a qualitative descriptive analytic research using various techniques including the process of observation, literature or documentation, and intensive interviews with the elite. The attitude of the political elite, Muhammadiyah and Nahdlatul Ulama in Surakarta have similarities such as supporting the implementation of the direct presidential elections as a logical consequence as citizens obedient to the law, on the other hand the attitude of the elite Muhammadiyah and Nahdlatul Ulama also have differences, between the elite who agreed and disagree implementation of direct presidential elections. Keywords: political attitudes, muhammadiyah, nahdlatul ulama.